DEVELOPMENT OF A TEST INSTRUMENT CONTAINING STEM COMPONENTS TO MEASURE ANALYTICAL THINKING SKILL IN TRIGONOMETRIC RATIOS - Cidi Cindiawati; Makmuri Makmuri; Flavia Aurelia Hidajat (Prima: Jurnal Pendidikan Matematika, 2026)
This study focuses on creating assessment tools to evaluate how well students can think analytically about math when dealing with trigonometric comparisons, assessing how accurate, consistent, and challenging each question is. Thirty-one students in the eleventh grade at SMAN 1 Rawamerta took part in this research. The 4D model was the method utilized for development, but it was streamlined to a 3D process (define, design, and develop). The assessment tool that was developed comprised four open-ended questions. Three college instructors and a seasoned teacher, acting as expert evaluators, examined the content, appearance, and structure of the test to ensure it was valid. Following the declaration of validity for the test tool, a small-scale trial was carried out to ascertain its real-world validity, dependability, and degree of difficulty. The expert validation results showed that this tool is highly valid, achieving a validity score of 97.92%. According to the calculations for real-world validity, this test instrument meets the criteria for good validity. The reliability test findings indicate good criteria with a calculated r value of 0.7363. Regarding difficulty, one question was classified as easy, while three questions were deemed to be of medium difficulty. Consequently, the assessment tool created can be considered suitable for use as a test containing STEM elements for gathering research data to gauge students' mathematical analytical thinking abilities. Furthermore, it is anticipated that educators can utilize this assessment tool as an evaluation material to thoroughly assess students' thinking capabilities at different stages.